Design, fabrication, and analysis of a precision drilling jig for waste reduction: a low-cost solution - Syed Mustafa Haider,; Abbas Hussain,; Shaheryar Atta Khan,; Naeem Sarwar,; Amir Nawaz, (Penerbit Universiti Kebangsaan Malaysia, 2024)
The modern assemblies of various machines such as engines, gears trains, and body panels require a highly precise drilling operation. These precisely drilled holes not only ensure the efficiency by constrained motions of these machines’ parts but also ensure longer service life. Moreover, precision drilling shall also ensure no subsequent requirement of reaming resulting in time and cost-saving. The precise drilling operation cannot be achieved unless highly precise machinery (CNC) is being utilized requiring higher initial investment (Pkr 1000000), or highly skilled workers demanding about twice the labor than the semi-skilled person. Being a small-sized industry, for profitability, a low-cost solution was proposed in this current work. To obtain precise drilling operation by the application of a drilling jig (Pkr 3000) on the manual bench drill machine (Pkr 15000), by a semi-skilled worker. In this work, a drilling jig has been designed, fabricated, and analyzed. This jig also can rotate the workpiece in clockwise/counter-clockwise directions. The drilled holes measurements provided the evidence that under the spindle speeds of 340, 700, and 1000 rpm, the closer dimensional values (~0.1mm) can be obtained, resulting in the elimination of rework and extra cost, along with the setup-time reduction by eliminating marking and center punching process, with the application of jig. It was concluded that the jig is quite applicable and can be substituted with high-cost CNC machines as a low-cost solution to the local small and medium-scale manufacturing industries.